2020
DOI: 10.1007/s00454-020-00231-x
|View full text |Cite
|
Sign up to set email alerts
|

On Grids in Point-Line Arrangements in the Plane

Abstract: The famous Szemerédi-Trotter theorem states that any arrangement of n points and n lines in the plane determines O(n 4/3 ) incidences, and this bound is tight. In this paper, we prove the following Turán-type result for point-line incidence. Let La and L b be two sets of t lines in the plane and let P = { a ∩ b : a ∈ La, b ∈ L b } be the set of intersection points between La and L b . We say that (P, La ∪ L b ) forms a natural t × t grid if |P | = t 2 , and conv(P ) does not contain the intersection point of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…, l ′ k ∈ L such that p i,j ∈ l i ∩ l ′ j . In [23], it was shown that any set of n points and n lines in the plane that does not contain a k × k-grid has at most O(n 4/3−ε ) incidences, where ε depends on k. A straightforward adaptation of Lemma 9 gives the following. Theorem 13.…”
Section: Discussionmentioning
confidence: 94%
“…, l ′ k ∈ L such that p i,j ∈ l i ∩ l ′ j . In [23], it was shown that any set of n points and n lines in the plane that does not contain a k × k-grid has at most O(n 4/3−ε ) incidences, where ε depends on k. A straightforward adaptation of Lemma 9 gives the following. Theorem 13.…”
Section: Discussionmentioning
confidence: 94%
“…As a corollary of Theorem 1.2 for k = 3, we get that there exists an arrangement of n points and n lines in the plane with no C 6 in the incidence graph while determining Ω(n 1+ 1 6 ) incidences. It is worth mentioning that one can follow the construction of Theorem 1.5 in [12] to get a construction of an arrangement of n points and n lines in the plane where their incidence graph is C 6 -free while it determines Ω(n 1+ 1 7 ) incidences.…”
Section: Discussionmentioning
confidence: 99%
“…A recent result of Mirzaei and Suk [13] can be seen as quantitative variant of Theorem 1.2, for specific types of subgraphs.…”
Section: Introductionmentioning
confidence: 95%